2024
DOI: 10.18063/ijb.729
|View full text |Cite
|
Sign up to set email alerts
|

Metrological characterization of porosity graded β-Ti21S triply periodic minimal surface cellular structure manufactured by laser powder bed fusion

Abstract: The design of a functionally graded porous structure (FGPS) for use in prosthetic devices is crucial for meeting both mechanical and biological requirements. One of the most commonly used cellular structures in FGPS is the triply periodic minimal surface (TPMS) structure due to its ability to be defined by implicit equations, which allows for smooth transitions between layers. This study evaluates the feasibility of using a novel β-Ti21S alloy to fabricate TPMS-based FGPS. This beta titanium alloy exhibits low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…TPMS split the space in two disjoint but intertwined regions [2]. This enables the construction of complex but highly symmetric porous structures for which the porosity may even be continuously varied in space in order to optimize the physical properties to a target application [1,3,4]. There are two ways to construct a bulk structure from a given TPMS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPMS split the space in two disjoint but intertwined regions [2]. This enables the construction of complex but highly symmetric porous structures for which the porosity may even be continuously varied in space in order to optimize the physical properties to a target application [1,3,4]. There are two ways to construct a bulk structure from a given TPMS.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that sheet networks for multimorphology geometries had higher elastic stiffnesses than solid networks. In another recent study on functionally graded gyroid TPMS structures Emanuelli et al [4] investigated the influence of density gradients on the static and cyclic compressive elastic moduli of additively manufactured b-Ti21S samples. They demonstrated that these elastic properties could be tailored to those of various kinds of bone tissues for future design of implants.…”
Section: Introductionmentioning
confidence: 99%